Geração de inovação em saúde a partir de pesquisas financiadas pelo Programa de Pesquisa para o SUS do Estado da Bahia - Macedo, Daiane Schultz (2022)
The Research Program for SUS (PPSUS) is a shared health management initiative that aims to support research aimed at solving priority health problems for the population. However, there are challenges in achieving the results established by the Program, such as the incorporation and use of the results of these researches in the SUS. In this context, the present study presents the following guiding question: what innovations were generated by research funded by PPSUS in the state of Bahia and were incorporated into the System? Therefore, the objective of this work was to analyze the results of research funded by PPSUS in the state of Bahia, in four editions already completed, regarding the verification of the generation of innovation in health and its application in the SUS. For this, the work was carried out from a qualitative research, with an exploratory descriptive character. Data collection consisted of three stages, the first being carried out on the documentary survey of project summaries approved by the PPSUS-BA notices, Nº 020/2010, Nº 020/2013, Nº 030/2013 and Nº 003/2017; the second, from the documentary survey of the final reports of the research projects; and the third, through a semi-structured interview with the research coordinators and operational managers of the PPSUS in the state of Bahia, including the actors of the Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB) and the Health Department of the State of Bahia. (SESAB). To organize and process the data, Lawrence Bardin's content analysis was used in the first and third stages of the research. The conduction of the analysis was structured in three chronological phases: pre-analysis; the exploration of the material; and the treatment of results, inference and interpretation. It can be concluded that the implementation of PPSUS in the state of Bahia contributed to scientific production, the training of human resources and made possible the articulation between the areas of health and science and technology, with the funding of important research for the state. However, of the 144 projects that were examined, only 15 resulted in potentially innovative technical innovations, but only three projects had results incorporated into the SUS. Another highlight is that the study advances in the field of health innovation methodologies, because there are no mechanisms in the literature that can categorize innovations in this field of knowledge. The study brings some recommendations for FAPESB and SESAB to create strategies to improve the process of incorporation of results to services, through adjustments in future project selection notices, creation of an information system for dissemination of results in the state and improvement in the operationalization procedures of the Program.